Improving Fine Motor Skills of Autistic Children Through Cotton Collage Activities at Special School in East Kutai Regency - Ilmiyah, Miftakul; Suparno, Suparno (Asian Journal of Social and Humanities, 2025)
This study aims to improve the learning outcomes and creativity of children with autism through cotton collage activities at the Special Needs School (SLB) in Kutai Timur Regency. The purpose of this research is to contribute to the development of effective, enjoyable, and appropriate learning methods tailored to the characteristics of children with autism. The research question focuses on how cotton collage activities can enhance the abilities of autistic children in collage-making. The learning process is designed to create an engaging and enjoyable atmosphere suited to the individual learning needs of autistic students. This research employs Classroom Action Research (CAR) conducted over three cycles. Data were collected through observations of student engagement, concentration, and participation throughout the activities. The results show improvements in fine motor skills and creativity, including the ability to recognize shapes, colors, and patterns, and to arrange cotton collage materials in a structured manner. These improvements also reflect an increase in student independence in completing tasks. The findings are expected to serve as a reference for teachers and educators in designing hands-on, activity-based learning with individualized approaches, which have proven effective in increasing interest and skills among children with autism.